An economic approach to improving water management in waterlogged and saline areas - Wichelns, Dennis, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Waterlogging and salinization arise in arid areas largely because two essential resources, irrigation water and the assimilative capacity of unconfined aquifers. are not priced or allocated correctly to reflect scarcity values and opportunity costs. Farm-level decisions regarding irrigation methods and water volumes will not be socially optimal when such values are not communicated to farmers in the prices they pay for irrigation and drainage resources, or in allocations that define their water supply or drainage capacity. Modifying farm-level prices and allocations may be helpful in reducing the rate of increase in waterlogged and saline areas in many regions. This paper describes why farm-level irrigation and drainage strategies often differ from those that would be considered socially optimal. In the absence of appropriate economic incentives, farmers are not encouraged to consider the off-farm and long-term impacts of their decisions regarding irrigation and drainage inputs. Policies that can be implemented to provide such encouragement include volumetric water pricing, water markets, tradable water allotments, adjustments in area-based cost recovery programs, and incentives for farmers to use irrigation methods that reduce deep percolation.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.